THE ALIGNMENT AND MISALIGNMENT OF THE ISLAMIC ECONOMICS CURRICULUM WITH THE INDONESIAN GOVERNMENT POLICY - Sutan Emir Hidayat; Sudarmawan Samidi; Atiqoh Nasution (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
The purpose of this paper is to explore the equivalency of curriculum content of universities. It examines how this equivalency can benefit the universities that offer Islamic economics programs in implementing the new policy of the Indonesian Education and Culture Minister, especially for point No. 4, known as "Merdeka Belajar: Kampus Merdeka" (Independent learning policy or Liberating policy). This study also evaluates whether or not the guidelines on implementing Islamic economic community involvement projects developed by the National Committee for Islamic Economy and Finance (Komite Nasional Ekonomi dan Keuangan Syariah - KNEKS) and other stakeholders can support the new policy, especially for point No. 4. This study uses content analysis from the curriculum of the ten selected universities in Indonesia that participated in developing the framework on minimum standardization across Islamic economics undergraduate programs led by KNEKS. The results of the study reveal that the ten universities are ready to implement the new policy of the Indonesian Education and Culture Minister, especially for point No. 4 known as "Merdeka Belajar: Kampus Merdeka" (Independent learning policy or Liberating policy) since a significant number of course equivalents were found across the ten universities. In addition, the guidelines on the implementation of Islamic economic community involvement projects developed by KNEKS are aligned with the new policy's guidelines on community involvement projects. The paper is expected to benefit several stakeholders, such as universities that offer Islamic economics programs, by providing them with guidelines on implementing the new policy. The student can use this study as a reference for them in conducting community involvement projects, internships, and student exchange programs.  ========================================================================================================ABSTRAK – Keselarasan dan Ketidakselarasan Kurikulum Ekonomi Islam dengan Kebijakan Pemerintah di Indonesia. Tujuan dari penelitian ini adalah untuk mengeksplorasi ekuivalensi dari isi kurikulum universitas dan melihat bagaimana ekuivalensi ini dapat memberikan bermanfaat bagi universitas yang menawarkan program ekonomi Islam dalam menerapkan kebijakan baru Menteri Pendidikan dan Kebudayaan Indonesia khususnya untuk poin No. 4 yang dikenal sebagai "Merdeka" Belajar: Kampus Merdeka” (Kebijakan belajar mandiri atau Kebijakan Pembebasan). Studi ini juga mengevaluasi apakah Panduan Pelaksanaan Kuliah Kerja Nyata (KKN) Tematik Ekonomi Syariah yang dikembangkan oleh Komite Nasional Ekonomi dan Keuangan Syariah (KNEKS) dan pemangku kepentingan lainnya dapat mendukung kebijakan baru terutama untuk poin No. 4 atau tidak. Penelitian ini menggunakan analisis isi dari kurikulum sepuluh universitas terpilih di Indonesia yang ikut berpartisipasi dalam mengembangkan Kerangka Acuan Akademik Program Studi S1 Ekonomi Syariah yang dipimpin oleh KNEKS. Hasil penelitian memperlihatkan bahwa 10 universitas siap untuk menerapkan kebijakan baru Menteri Pendidikan dan Kebudayaan Indonesia khususnya untuk poin No. 4 yang dikenal sebagai "Merdeka Belajar: Kampus Merdeka" (kebijakan belajar mandiri atau kebijakan Pembebasan) karena ditemukan banyak mata kuliah yang memiliki ekuivalensi diantara 10 universitas. Selain itu, Panduan Pelaksanaan KKN Tematik Ekonomi Syariah yang dikembangkan oleh KNEKS ditemukan selaras dengan panduan kebijakan baru terkait program membangun desa/Kuliah Kerja Nyata Tematik. Artikel ini diharapkan bermanfaat bagi beberapa pemangku kepentingan seperti universitas yang menawarkan program ekonomi syariah dengan memberi mereka pedoman tentang bagaimana menerapkan kebijakan baru. Mahasiswa dapat menggunakan studi ini sebagai referensi bagi mereka dalam melakukan proyek pembangunan desa, magang, dan program pertukaran pelajar.